An Analysis of Students’ Problem with Reading Comprehension at The Eleventh Grade Student of Senior High School 2 Muaro Jambi - Vienendra, Ridwan; Wennyta, Wennyta; Fitri, Nurul (Universitas Batanghari Jambi, 2024)
The purpose of the research is to find out students' problems with reading comprehension in the eleventh grade of Senior High School 2 Muaro Jambi. The research utilized qualitative questionnaires as an approach method. The population consisted of XI IPA students at SMAN 2 Muaro Jambi for the 2023 academic year and the sample consisted of 28 students from class XI IPA 3. The researcher used a research instrument in the form of a questionnaire in a predetermined form, namely a questionnaire. To find out these findings, tabulations were used to collect data from student scores to categorize 8 indicators of 16 questions and 5 student items that they answered and selected. After the results of the data are found, a classification of student scores is carried out using the Likert scale from Jamieson (2017). Based on the research findings, the indicators out of 8 were divided into 16 questions and the 5 items of reading comprehension ability they chose were Strongly agree (16%), Agree (34%), Undecided (3%), Disagree (2%), Strongly disagree (0%). have an average value agree. However, the overall average by the sum of all 5 items was summed and the result (89,6) is Strongly Agree. Furthermore, students' ability in reading comprehension gets a score of 59% which has been added to the Strongly Agree category. This shows that the level of ability in reading comprehension of students is in Strongly Agree, and it shows that the score in reading comprehension is still in Strongly Agree.Keywords: Students ability, reading comprehension